Prognostic value of cardiac magnetic resonance–derived global longitudinal strain in LGE-negative dilated cardiomyopathy - Tian-Yue Zhang; Tian Lan; Ling-Li Wang; Yu-Cong Zheng; Xin-Yi Feng; Fei-Yao Wang; Fan Zhang; Hua-Yan Xu; Xi Liu; Zhi Yang; Rui Li (PLoS ONE, 2026)
Background Dilated cardiomyopathy (DCM) is a major cause of heart failure and sudden cardiac death (SCD), with a 5-year survival rate of approximately 45%–50%. Current risk stratification is predominantly dependent on left ventricular ejection fraction (LVEF), which has limited sensitivity and specificity. Hence, more effective biomarkers should be used in late gadolinium enhancement (LGE)-negative patients. Methods A total of 378 consecutive patients with LGE-negative DCM were enrolled from four hospitals between December 2016 and December 2022. Cardiac magnetic resonance imaging-derived strain parameters (global radial strain, global circumferential strain, and global longitudinal strain [GLS]) were assessed against the primary (SCD and related events) and secondary (heart failure, appropriate implantable cardioverter-defibrillator therapy) endpoints. Internal validation was performed using stratified bootstrap resampling with Harrell’s optimism correction to report the optimism-corrected C-index. Data were accessed for research purposes from 15/06/2023–30/12/2023, and all records were de-identified prior to analysis. Results Over a median follow-up of 59.78 months, 35 (9.26%) and 72 (19.0%) patients presented with the primary and secondary endpoints, respectively. Based on the multivariate Cox analysis, GLS, LVEF, and age were independent prognostic factors. However, only GLS (HR = 1.37; P = 0.041) remained significant in the LVEF <20% subgroup. A model integrating GLS and LVEF had a better discrimination ability for SCD than LVEF strata alone (apparent C-index 0.756 vs 0.714, P < 0.001). This advantage persisted after bootstrap internal validation (B = 1000; optimism-corrected C-index 0.754 vs 0.711, Holm adjusted P = 0.048). Further inclusion of age and New York Heart Association (NYHA) classification enhanced the model’s performance (model 4): apparent C-index 0.801; optimism-corrected C-index 0.785). Conclusion GLS is an independent predictor of SCD-related events in LGE-negative DCM. Incorporating GLS with conventional indicators such as age, NYHA classification, and LVEF significantly enhances prognostic discrimination and model robustness, indicating potential value for future clinical risk stratification.